PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA - Neliwati; Irfan; Fira Dwi Putri; Muliana Putri; Abdi Syahputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore how the use of Augmented Reality (AR)–based learning media can enhance students’ learning motivation and learning outcomes. Using a qualitative approach, the research examines students’ experiences, perceptions, and responses to the implementation of AR media in the learning process. Data were collected through in-depth interviews, participatory observation, and documentation studies involving secondary school students who used AR-based learning media for one semester. Data analysis was conducted thematically to identify patterns of change in students’ motivation and learning achievement. The findings indicate that AR-based learning media provide more engaging and interactive learning experiences, thereby increasing students’ intrinsic motivation. Furthermore, the use of AR media facilitates a better understanding of concepts, which is reflected in a significant improvement in learning outcomes. This study recommends broader integration of AR media in learning as an innovative strategy to improve the quality of education.